2012
DOI: 10.1017/s1041610211002729
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing commencement and adherence to a home-based balance exercise program for reducing risk of falls: perceptions of people with Alzheimer's disease and their caregivers

Abstract: A home-based exercise program with regular support from a physiotherapist and caregiver are key elements facilitating continuing program adherence in people with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 19 publications
2
92
0
1
Order By: Relevance
“…Studies have shown that potential benefits of the program, recommendations of health professionals, support of caregivers, friends and family and activities that provide social interaction and enjoyment are factors that affect the participation of older adults in fall prevention programs. 18,19 The higher prevalence of fall prevention practices in the older adult men in this study, can probably be explained by the fact that the older adult men felt more vulnerable. This may mean that more men are interested in prevention activities, including those for falls.…”
Section: Discussionmentioning
confidence: 80%
“…Studies have shown that potential benefits of the program, recommendations of health professionals, support of caregivers, friends and family and activities that provide social interaction and enjoyment are factors that affect the participation of older adults in fall prevention programs. 18,19 The higher prevalence of fall prevention practices in the older adult men in this study, can probably be explained by the fact that the older adult men felt more vulnerable. This may mean that more men are interested in prevention activities, including those for falls.…”
Section: Discussionmentioning
confidence: 80%
“…In this review, adherence to the exercise regimen for individuals with dementia ranged greatly between studies and explicit reasons why exercise adherence was low were not always reported. Suttanon et al (2012) and Suttanon et al (2013) conducted a detailed analysis, interviewing the persons with dementia and caregivers included in a randomized clinical trial investigating the effect of a home-based exercise programme for older people with AD. They found that preexisting or acute health conditions, a dislike of structured exercise, and caregiver causes (health and unavailable) were reasons for lower levels of adherence and concluded that regular support from a physiotherapist and caregiver were key elements facilitating program adherence in people with AD (Suttanon et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Suttanon et al (2012) and Suttanon et al (2013) conducted a detailed analysis, interviewing the persons with dementia and caregivers included in a randomized clinical trial investigating the effect of a home-based exercise programme for older people with AD. They found that preexisting or acute health conditions, a dislike of structured exercise, and caregiver causes (health and unavailable) were reasons for lower levels of adherence and concluded that regular support from a physiotherapist and caregiver were key elements facilitating program adherence in people with AD (Suttanon et al, 2012). Behavioral and cognitive strategies have been reported to increase the adherence to exercise (Woodard & Berry, 2001) and cognitive behavioral therapy has also been shown to be effective in reducing symptoms of depression and anxiety for people with dementia (Orgeta, Qazi, Spector, & Orrell, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Caregivers provide encouragement to undertake risk reduction strategies (29), particularly important for a person with dementia with variable memory capacity. They also physically assist with exercise programs (10) and play a role in negotiating hazard reduction and risk-taking behaviors (31). The caregiver’s role in falls prevention is increasingly important as the dementia process continues and, while this role is often reliant on a caregiver’s personal characteristics, it may actually relate more to active engagement of the caregiver and method of intervention delivery (15).…”
Section: Discussionmentioning
confidence: 99%